Requisitos para a preservação da memória institucional: uma análise sob a perspectiva dos editais de ingresso e reingresso de alunos na UFSM - Prade, Aline Márcia (2023)
The urgency of thinking about actions aimed at preserving and providing access to cultural heritage through authentic, reliable and trustworthy documents motivated the choice of the research topic presented to the Postgraduate Program in Cultural Heritage, based on the research line Documentary Archival Heritage. The objective of this study is to propose a Draft Normative Instruction and a Manual of procedures for the Production, Description and Dissemination of notices within the scope of Universidade Federal de Santa Maria (UFSM), based on the analysis of the notices of admission and re-entry of students in undergraduate courses. As for the methods, this is a qualitative research, of an applied nature, with an exploratory character, carried out through documentary research and observation, where the admission and re-entry notices are part of the case study that will support the development of this research. To achieve the objectives, meetings were first held between the Departamento de Arquivo Geral (DAG) and the Pró-Reitoria de Graduação (Prograd), through the Coordenadoria de Oferta e Relacionamento (Cofre), in order to align expectations regarding the research and define the actions to be taken during the study. In the next step, the rules for the opening of the Administrative Process for the Approval of Public Notices were defined, given the need to sign the public notices for admission and re-entry of undergraduate students digitally, through the Document Portal. Then, it was realized the need to standardize the main documents that make up the admission and re-entry process, in addition to developing a tutorial to guide candidates regarding changes in the filing of appeals to the result of the selection process. The third stage of the research was dedicated to training the Cofre team in relation to the procedures for the production, description and dissemination of admission and re-entry notices, in addition to training the civil servants responsible for the Institution's Undergraduate Course Secretariats regarding changes in the procedures for filing appeals to the result of the selection process. The analysis and standardization of procedures related to the selection process for admission and re-entry led to the preparation of the Draft Normative Instruction and the Manual of procedures for the Production, Description and Dissemination of public notices within the scope of UFSM. As a result, it was found that the elaboration of regulations related to the production, description and dissemination of permanent custody documents is still incipient in the Institution. This research brings practical solutions to be applied to notices, aiming at their preservation and access. However, there is still a vast field of work to be explored in relation to the awareness and training of the university community regarding the use of the Document Portal for the production, description and dissemination of documents, in order to keep them preserved and accessible for as long as necessary.